Lateral extra‐articular procedures combined with ACL reconstructions lead to a higher return to pre‐injury level of sport: A systematic review and meta‐analysis - Guus Felix Kerkvliet; Gijs Bram Peter Cornelis van derRee; Inger Nicoline Sierevelt; Gino M. M. J. Kerkhoffs; Bart Muller (Journal of Experimental Orthopaedics)
Abstract Purpose To compare postoperative activity levels between patients who received an anterior cruciate ligament reconstruction (ACLR) with‐ and without a lateral extra‐articular procedure (LEAP). Objectives The primary objective is to examine whether patients treated with an ALCR and LEAP have a greater chance to return to sport (RTS) and return to their pre‐injury level of sport (RTPS). The re‐rupture rates between the two groups will also be analysed as this is of great influence on the RTS and RTPS. Methods A thorough search according to PRISMA guidelines was conducted through the PubMed and Embase databases in May 2024. Randomised controlled trials (RCT) and retrospective cohort studies on patients who underwent primary ACLR with‐ or without a LEAP were included. Postoperative Tegner score, RTS, RTPS and re‐rupture rate were evaluated. All articles were revised according to Cochrane risk of bias tools (RoB 2.0 and ROBINS‐I). Results Twenty‐four studies were included after examining 966 titles, abstracts and manuscripts. A total of 33,527 patients were included in this review with a weighted mean age of 24.9 years. Pooled data demonstrates that the ACLR + LEAP group shows significantly higher postoperative Tegner scores (MD, 0.43 [95% confidence interval, 0.21–0.65]; p < 0.01). 62% of patients who underwent ACLR + LEA returned to their pre‐injury level of sport compared to 40% in ACLR group (reported in nine studies). Conclusion This meta‐analysis demonstrates that patients undergoing a LEAP procedure in addition to ACLR return to higher postoperative activity levels and are more likely to return to their pre‐injury level of sport. These results ‐in addition to further research‐ may help dictate when to add a LEAP, and whether LEAP in addition to ACLR should become the golden standard. Level of Evidence Level III, retrospective cohort studies have been analysed, alongside RCT's, and thus this is the level of evidence.